2020
DOI: 10.4236/ojog.2020.101004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Insertion with the New Inserter of the Intra-Uterine Device of the Postpartum at the Referral Health Center of Commune II of Bamako, Mali

Abstract: Background: In Mali, contraceptive prevalence is low, while the unmet need for family planning is very high. Postpartum contraception can help to significantly reduce these unsatisfied needs. The introduction of the intrauterine device (IUD) in the postpartum quickly encountered problems with the type of forceps used to make the insertions (Kelly or Heart forceps), and also their availability at the various health centers. Thus, in 2016, the Population Services International Mali (PSI-Mali) introduced the inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
1
4
1
Order By: Relevance
“…Spontaneous miscarriage: the frequency of abortion is 8.28% in our study. This rate is much lower than the results of other studies; Dao SZ, a Danish study [5] [9] [10], which respectively found L 15% and 54% miscarriage, while the overall risk is 8% at 22 years [3]. In our study, there is no associative link between the occurrence of ectopic pregnancy and maternal age, i.e.…”
Section: Characteristics Of Pregnancycontrasting
confidence: 83%
See 2 more Smart Citations
“…Spontaneous miscarriage: the frequency of abortion is 8.28% in our study. This rate is much lower than the results of other studies; Dao SZ, a Danish study [5] [9] [10], which respectively found L 15% and 54% miscarriage, while the overall risk is 8% at 22 years [3]. In our study, there is no associative link between the occurrence of ectopic pregnancy and maternal age, i.e.…”
Section: Characteristics Of Pregnancycontrasting
confidence: 83%
“…This high rate corresponds to the results of many other series, Jo-Ann Johnson et al, AUDIPOG, Audrey Meyer respectively, Panel A et al[1] [18][21] [22] 50%, 43%, 40%, 43, 5%. In their study Dao SZ[5] et al found a lower cesarean section rate; its cesarean rate is 16.7%, three times higher in exposed patients than in unexposed patients, i.e. 5.8%.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The same postoperative complications were reported in lower proportions than ours by: Dao S.Z. et al [13] with 1.81% of parietal suppuration, 1.44% of endometritis; Traoré S. et al [6] with 1.9% of parietal suppuration and 1.3% of anemia; 2.6% of endometritis.…”
Section: ) Maternal Prognosissupporting
confidence: 79%
“…Of these, 284 cases died, a frequency of 4.2%. This frequency is higher than: from Thiam O [6] in Senegal in 2013, Seydou Z et al [7] in 2018 to CS Ref Commune II in Bamako, Mali, Touré S in 2019 in Banamba [8] which reported respectively 2%; 0.4% and 0.7%. The frequency of maternal deaths among evacuees is variously assessed, depending on the method of recruitment, the area and the duration of study.…”
Section: Discussionmentioning
confidence: 68%